2022
DOI: 10.3390/pharmaceutics14051019
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-Eluting Contact Lenses Effect on Tear Volume: In Vitro and In Vivo Experiments

Abstract: (1) Background: The purpose of this study was to synthesize melatonin-eluting contact lenses (CLs) and evaluate both the ocular kinetics of the released melatonin and its effect on tear volume and intraocular pressure. (2) Methods: In vitro, melatonin-eluting CLs were synthesized by using non-functionalized (HEMA) and functionalized (HEMA/APMA) monomers. In vivo, a short-term prospective and randomized study was performed on 15 rabbits divided into two groups: 12 rabbits wearing functionalized CLs and 3 rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Regardless, using CLs as a vehicle of melatonin analog delivery could reduce the dose of these secretagogue agents, avoiding possible adverse effects. Serramito et al demonstrated, by using the Draize test, that melatonin at the same concentration ranked similar to the one employed in our in vivo studies (micromolar range) did not provoke corneal adverse effects in rabbits [ 45 ]. Furthermore, another study confirmed the good ocular tolerance of melatonin at the millimolar range of concentration in a different animal model [ 22 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Regardless, using CLs as a vehicle of melatonin analog delivery could reduce the dose of these secretagogue agents, avoiding possible adverse effects. Serramito et al demonstrated, by using the Draize test, that melatonin at the same concentration ranked similar to the one employed in our in vivo studies (micromolar range) did not provoke corneal adverse effects in rabbits [ 45 ]. Furthermore, another study confirmed the good ocular tolerance of melatonin at the millimolar range of concentration in a different animal model [ 22 ].…”
Section: Discussionmentioning
confidence: 56%
“…Given the more potent secretagogue effect obtained via the delivery of CLs versus the topical route, the melatonin released by soaked CLs could trigger that effect in vivo. Indeed, Serramito et al recently demonstrated that the melatonin-loaded CLs produced by solvent casting evoked a marked secretagogue effect in rabbits [ 45 ]. This method of drug incorporation has emerged to overcome the main problems associated with the soaking protocol [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[84] In particular, the ubiquitous presence of membrane melatonin receptors in the eye has prompted many researchers to investigate the efficacy of melatonin and its analog in treating DED. [85] Past evaluations of melatonin analogs on animal models with DED have shown a restoration of tear homeostasis and a reduction in inflammation and oxidative stress. To further confirm this, Navarro-Gil et al explored the potential of contact lenses loaded with melatonin analogs in treating DED.…”
Section: Tear Film Improving Agent Deliverymentioning
confidence: 99%
“…Previous research has shown that melatonin may be a powerful agent in stimulating tear production [84] . In particular, the ubiquitous presence of membrane melatonin receptors in the eye has prompted many researchers to investigate the efficacy of melatonin and its analog in treating DED [85] . Past evaluations of melatonin analogs on animal models with DED have shown a restoration of tear homeostasis and a reduction in inflammation and oxidative stress.…”
Section: Ophthalmic Applications Of Hydrogelsmentioning
confidence: 99%
“…To provide our readers with more comprehensive information, we have compiled a list of drugs that can be contained in contact lenses (Table ). ,,− …”
Section: Therapeutic Sclsmentioning
confidence: 99%